The predictors of the behavioral intention to the use of urban green spaces: The perspectives of young residents in Phnom Penh, Cambodia. (June 2017) - Yen, Yat; Wang, Zhanqi; Shi, Yumin; Xu, Feng; Soeung, Bunly; Sohail, Muhammad Tayyab; Rubakula, Gelas; Juma, Sahim Abdalla
Abstract: Urban green spaces (UGSs) play a major role in enhancing the well-being and recreation areas for the urban dwellers; however, there is a very limited study of this field in Cambodia. In response to an increasing demand for recreational areas among urban dwellers, this study investigated the behavioral intention to the use of the UGSs from the perspective of the young residents of Phnom Penh using the Theory of Planned Behavior (TPB). The perceived safety, accessibility, and usefulness and the core constructs of TPB were conceptualized to predict their effects on behavioral intention. In all, 554 completed samples were collected from both online and face-to-face interviews among the respondents. Data were empirically analyzed using the partial least squares structural equation modeling (PLS-SEM) approach and SmartPLS 3.0 software. The results revealed that the behavioral intention to the use of the UGSs was significantly associated with the perceived safety and personal attitudes, but it was not significantly associated with perceived accessibility and usefulness. The safety of the UGSs is a critical concern that recoils the behavioral intention while a lack of basic knowledge regarding the usefulness and roles of the UGSs makes negative attitudes toward the behavioral intention. It is, therefore, the safety of the UGSs that should be ensured so as to foster a livable city as well as to promote the use of the UGSs. Highlights: The study examined the main predictors of the behavioral intention to use UGSs among young residents of Phnom Penh. Of the total respondents, 89.76 % had very strong behavioral intention to use UGSs but 75.34% found UGSs difficult to access while 93.77% very concerned about the safety when they visited UGSs. The behavioral intention has a positive significance with the attitudes vice versa it has a negative significance with the perceived safety. The safety of UGSs is a critical concern that recoils the behavioral intention while lacking basic knowledge of UGSs leads to the negative attitudes toward behavioral intention.